2019 IEEE/ACM 41st International Conference on Software Engineering (ICSE) 2019
DOI: 10.1109/icse.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable is the Crowdsourced Knowledge of Security Implementation?

Abstract: Stack Overflow (SO) is the most popular online Q&A site for developers to share their expertise in solving programming issues. Given multiple answers to certain questions, developers may take the accepted answer, the answer from a person with high reputation, or the one frequently suggested. However, researchers recently observed that SO contains exploitable security vulnerabilities in the suggested code of popular answers, which found their way into security-sensitive highprofile applications that millions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Education Could certainly do better [48], though there are encouraging signs [49] and useful ideas when it comes to improving informal resources [59]. However, informal resources can be dangerous when it comes to security, and [49] recommends giving all students the advice in [60]: "If you pick up a SSL/TLS answer from Stack Overflow, there's a 70% chance it's insecure".…”
Section: Discussionmentioning
confidence: 99%
“…Education Could certainly do better [48], though there are encouraging signs [49] and useful ideas when it comes to improving informal resources [59]. However, informal resources can be dangerous when it comes to security, and [49] recommends giving all students the advice in [60]: "If you pick up a SSL/TLS answer from Stack Overflow, there's a 70% chance it's insecure".…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al found that one third of SO posts contain potential API misuses [47]. Chen et al found that a large proportion of security implementations on SO is insecure, and that the corresponding posts have higher scores and more duplicates compared to posts with secure suggestions [15]. In the future, we also plan to investigate the quality of unocial performance-related information from crowdsourced data.…”
Section: Knowledge In Documentationmentioning
confidence: 97%
“…Based on best of our knowledge, this is the first study on security of C# codes. several studies investigated security related issues in languages like Java and Python [22], [11], [5]. However, as mentioned no study has focused on security of C# codes and thus no study on C# code snippets in community question and answer websites exist.…”
Section: Related Workmentioning
confidence: 99%